An analysis of precipitation in Lattakia station (1980- 2010) - Fayad, Rim (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In this study, the Analysis statistical of the annual, seasonal and monthly rainfall values were performed in Lattakia station (northwest of Syria) during the period (1980- 2010) using particular statistical methods . The results of this study showed a reasonable authenticity of annual precipitation rate (coefficient of variance 26%), with a degradation of annual amount of precipitation during the study period (12.8%). The possibility of daily rainfall reached (28.6%) during the rainy months, in addition, the incidence frequency of the drought years was more than the humid years during the study period.